2023
DOI: 10.1111/1471-0528.17451
|View full text |Cite
|
Sign up to set email alerts
|

International multi‐stakeholder consensus statement on clinical trial integrity

Abstract: Objective To prepare a set of statements for randomised clinical trials (RCT) integrity through an international multi‐stakeholder consensus. Methods The consensus was developed via: multi‐country multidisciplinary stakeholder group composition and engagement; evidence synthesis of 55 systematic reviews concerning RCT integrity; anonymised two‐round modified Delphi survey with consensus threshold based on the average percentage of majority opinions; and, a final consensus development meeting. Prospective regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…There have been several separate strategies proposed to prevent the publication of flawed RCTs and systematic reviews. [5][6][7][8][9][10][11][12][13][14][15][16] We have agreed to implement a bundle of strategies 17 which will be required upon submission to our journals (Table 1). Nonadherence to these criteria will result in rejection.…”
Section: Prevention Of Publication Of Untrustworthy Datamentioning
confidence: 99%
“…There have been several separate strategies proposed to prevent the publication of flawed RCTs and systematic reviews. [5][6][7][8][9][10][11][12][13][14][15][16] We have agreed to implement a bundle of strategies 17 which will be required upon submission to our journals (Table 1). Nonadherence to these criteria will result in rejection.…”
Section: Prevention Of Publication Of Untrustworthy Datamentioning
confidence: 99%
“…This is now routine in effectiveness reviews. The development, validation, and application of advanced methods that can accurately detect integrity breaches in publicly available RCTs are needed [ 43 , 44 , 45 ]. Handling the integrity assessment of selected studies after excluding those with confirmed integrity breaches requires further consideration in methodological development of evidence syntheses as, at present, there are no clear procedures established.…”
Section: Implications Issues Challenges and Limitationsmentioning
confidence: 99%
“…There have been several separate strategies proposed to prevent the publication of flawed RCTs and systematic reviews. [5][6][7][8][9][10][11][12][13][14][15][16] We have agreed to implement a bundle of strategies 17 which will be required upon submission to our journals (Table 1). Non-adherence to these criteria will result in rejection.…”
Section: Pr Ev E N Tion Of Pu Bl Ication Of U N T Rust Wort H Y Datamentioning
confidence: 99%